Study of Engine Operation Features Depending on the Boiling Point of Gasoline for Hot Climates - Alimova Zebo Hamidullayevna; Sabirova Dilorom Kabulovna; Niyazova Gulkhayo Parpiyevna (Zien Journals, 2022)
The article analyzes the dependence of the wear of engine parts on the evaporation temperature of gasoline. It is known that only the fuel that is in a gaseous state burns in engines. Therefore, for the completeness of combustion, it is necessary that the entire liquid phase of the fuel passes into a vaporous phase, and there is a thorough mixing of fuel vapors with air to form a combustible mixture. To ensure optimal engine operating conditions in hot climatic conditions, we suggest that the temperature of the beginning of the distillation of gasoline boiling should not be lower than 400С ÷ 430С, the distillation temperature of 10% gasoline should not be lower than 700C, also the boiling of 90% should not be higher than 180°C, and the temperature of the end of distillation is 195 °С.
Keywords: gasoline evaporation; engine parts wear; combustion completeness; piston rings